Yoga como caminho de elevação na espiritualidade e na saúde - Lima, Vânia Cristina Lucena (2010)
This current study portray a research conducted in João Pessoa, PB, during the period November 2009 to October 2010, under the qualitative methodology Oral History of Life. The purpose were analyze the Yoga meaning like a spiritual development way and health; delineate a historical route of yoga from India to their beginner in Paraíba; analyze the benefits of this practice in mental and physical health of the collaborators Ada Tavares Zenaide, Mercia Rios Ribeiro and Maria Cristina Correia de Abreu, and identify how these collaborators transmitted this knowledge of yoga to the community of Joao Pessoa. In this way, it was possible to better understand the meaning of yoga within a socio-historical perspective; This allowed enlarge clarity on its prehistory and history, but also allowed us to know through the authors, like Lílian Gulmini, Iyengar, Paulo Rosas, Hermógenes, Possebom, Cristina Abreu, among others, the philosophical tradition of yoga as an axis directed toward the elevation of spirituality and physical and mental health. In the study results were identified by the three methods used by collaborators: the Iyengar Yoga (Ada), Tantra Yoga (Mercia) and Hatha Yoga (Cristina). Regarding the increase in physical health, Cristina found that through the practice of yoga on exercise, the correct way of breathing, feeding and meditation, there was a change in their lifestyle, which enabled her to recover a deep anemia and the reorganization of the functioning of your body. Ada applies knowledge of Yoga with comfort, affection and zeal to promote the health of their students, theirs column unstiffening of the body and apply relaxation techniques, physical comfort as the triggers emotional comfort. Mercia said it was a healthy person, when she does their assessments with clinician, he does not prescribe medications because she does not need. From the standpoint of mental health, Cristina most learned to respect herself and the others, to relax, to escape from the stresses of daily life, experiencing the present moment. Ada believes his longevity is a result of yoga practice, for without this experience, she says would've died, to be its emotional heart could not bear the pangs of life due to the accumulation of negative emotions. Regarding the rise of spirituality - Ada reported that yoga in his life was one way to find God or a release. So Through this study, there was the finding that the beneficial effects of yoga suggested a real possibility of change in quality of life of the three collaborators, they lived life experiences so rich in meanings, which would be evidenced in the increase in physical health, mental and spirituality, the results are consistent with the goals outlined in this research. We conclude that there is a gap in the training of professionals, especially in education and health, requiring a potential scope for public policy.